PRAKTEK PENGELOLAAN DANA DESA DI DESA SIDOREJO KECAMATAN SAYUNG KABUPATEN DEMAK - Alimin, Alimin; Astuti, Retno Sunu (Journal of Public Policy and Management Review, 2018)
The policy of raising the ceiling of the village funds by the Central Government has an impact on the incomplete problem of village apparatus managing the huge amount of village funds, as for the problems in Sidorejo Village is the unregulated budget discipline and unaccountable namely the late disbursement of village funding phase 1 phase 2 of budget year 2016 and not yet a consolidated report, with alleged problems in the competence of village apparatus and organizational culture. This study aims to determine the practice of managing village funds in Sidorejo Village, District Sayung, Demak. The research approach is qualitative, there are 3 observed research phenomena which are about the performance of village fund policy, organizational culture and competence. The indicators of village fund management include: effectiveness, equity and responsiveness. Methods of data collection is direct observation and interview. The result of the research shows that the management of village fund in Sidorejo Village is still not good, it can be seen from indicator of effectiveness and equity which still not maximal. The practice of village fund management in Sidorejo Village that has not been well influenced by the competency factor of village apparatus includes the skills and knowledge of the village fund management system which is lacking, other factors that influence the organizational culture include the absence of reward system and the lack of training and development of village apparatus. The recommendation in this research is the existence of organized training and development and the existence of system of reward/intensive for apparatus having good competence.